EVALUASI PENERAPAN PAJAK PERTAMBAHAN NILAI ATAS AGUNAN YANG DIAMBIL ALIH (PPN AYDA) DI PT BPR KARYA BAKTI SEJAHTERA - Kumala, Ratih; Sumarta, Rian; Hidayatullah, Eka Nur (Universitas Dharmawangsa, 2025)
Foreclosed Assets (AYDA) refer to assets acquired by banks from debtors who have defaulted on their credit obligations, and such transfers are subject to Value Added Tax (VAT). The implementation of VAT on AYDA has significant implications for the banking sector, particularly in terms of income and operational costs. This study aims to evaluate the implementation of VAT on AYDA at PT BPR Karya Bakti Sejahtera. The research employs a descriptive qualitative method. The results indicate that while the bank has established standards and procedures for implementing VAT on AYDA, the actual implementation remains inconsistent. This is evidenced by the fact that out of four AYDA transactions, only one was properly subjected to and reported for VAT. Additional challenges include limited technical understanding, unintegrated recording systems, and the diverse nature of collateral assets. Nevertheless, the bank has undertaken corrective measures through staff training, SOP revisions, and the enhancement of its information systems.